Avalia??o de sentimentos e aprendizagem de estudantes de programa??o introdut?ria em uma abordagem h?brida com PBL - Souza, Suenny Mascarenhas (2021)
Learning programming can be difficult and challenging, given the worrying dropout and failure rates in introductory programming courses. Students? sentiments are considered relevant factors linked to these difficulties and have an influence on learning. This work evaluates students? sentiments and their performance in an integrated course of introductory programming (CS1) whose teaching approach uses lectures and the Problem-Based Learning (PBL) method, in the first semester of the Computer Engineering program at the State University of Feira de Santana (UEFS). We explored, in a case study, the relationship between motivation, engagement and students? attitudes with their performance. In a confirmatory analysis, we also compared students? performance and sentiments when using different programming languages: C and Python. Results suggest that students are positively motivated when they experience the hybrid approach. However, within this approach, engagement did not seem expressive. Meanwhile, students also seem to maintain positive attitudes after the integrated course. Also, motivation is different in PBL tutorials compared to lectures, while engagement is similar in both methods. As for students? performance, it remains median throughout the semester, but is relatively better in PBL tutorials when compared to lectures. Regarding the relationships between sentiments and student performance, results suggest that motivation is capable of predicting students? learning outcomes within the adopted teaching approach. Confidence and Satisfaction categories are the most predictive. On the other hand, engagement does not seem to predict learning results as much, especially in lectures. Even so, Dedication and Vigor seem to have a certain relationship with performance. Regarding attitudes, results suggest a certain importance for Confidence and Interest categories. Confirmatory analysis also suggests that there is no difference in either students? performance or sentiments when they experience the hybrid PBL approach either with C or Python. Only the sense of usefulness seems to be higher with the C language. We believe that these results can help understand the factors that may lead to the difficulties faced by students in introductory programming courses. They may also help foster better teaching practices, both in lectures and in the PBL method. Furthermore, results of this work can aid in understanding the experience lived by CS1 students within a hybrid PBL approach with either C or Python languages.